British representations of the Armenian Genocide, 1915-23 - Morgan, Peter, 1967- (New York, NY : Routledge, 2025)
"This book examines how British politicians, national and local newspapers, writers and commentators discoursed on the mass killing and deportation of Armenians during the period 1915-23. Seeking to fill a historiographical gap in the field of modern genocide studies, this volume shows the extent to which the British public sphere understood the concept of genocide before the Holocaust and before the word itself was invented. It demonstrates the centrality of the British discourse on the Armenian massacres and deportations as they were happening during the First World War and how it came to be as important as that on German excesses in Belgium. This book reveals for the first time how the news was widely circulated in the provincial press and not just in contemporary major titles, and how it found its way into everyday conversation and the subject of an adventure novel. In analysing how the violence was viewed as an orientalist projection onto the Turkish 'Other,' this volume makes an important contribution to literature on the more troubling side of the 'British Self' and imperial colonialism. This volume will be of interest to undergraduates studying First World War Britain as well as researchers investigating the development of modern genocide and how it was discussed and conceptualised"--
British Representations of the Armenian Genocide During the First World War Alongside German 'Frightfulness' -- British Representations of an Idealised Armenian Peasantry Living in a Rural Idyll and its Despoliation by the 'Turk' -- Biomedical Language and Scientific Rationales in British Representations of the Armenian Genocide -- British Representations of the Armenian Massacres and Deportations as a Process of Systematic Extermination.
Includes bibliographical references and index.
Keywords: Armenian Genocide, 1915-1923 -- Foreign public opinion, British; Armenian Genocide, 1915-1923 -- Press coverage -- Great Britain; Armenian Genocide, 1915-1923 -- Historiography; World War, 1914-1918 -- Great Britain -- Propaganda; World War, 1914-1918 -- Atrocities -- Belgium; World War, 1914-1918 -- Influence; Propaganda, British -- History -- 20th century; Public opinion -- Great Britain; Total war